Utilisation of maltose and glucose by lactobacilli isolated from sourdough - Stolz, P. (Hohenheim Univ., Stuttgart (Germany). Inst. fuer Lebensmitteltechnologie); Boecker, G; Vogel, R.F; Hammes, W.P (FEMS microbiology letters, 1993)
The utilisation of glucose and maltose was investigated with Lactobacillus strains isolated from sourdough starters. These preparations have been in continuous use for a long period to produce sourdough from rye, wheat and sorghum. The major metabolic products formed by resting cells from glucose or maltose were lactate, ethanol and acetate. Upon fermentation of maltose, resting cells of Lactobacillus sanfrancisco, L. reuteri, L. fermentum and Lactobacillus ep. released up to 13.8 mM glucose after 8 h. The ratio of released glucose per mol of utilised maltose was up to 1:1. Glucose formation was high when starved cells of L. sanfrancisco and Lactobacillus sp. were used. This is consistent with maltose utilisation via maltose phosphorylase which phosphorylates maltose without the expenditure of ATP and thus allows the cell to waste glucose in the presence of abundant maltose. The glucose formed may be utilised by the lactobacilli or other microorganisms, e.g. yeasts. However, the release of glucose into the medium by sourdough lactobacilli prevents competitors from utilising the abundant maltose by glucose repression. In strains of L. sanfrancisco, maltose utilisation was very effective and not subject to glucose repression. Therefore, they overgrow other microorganisms sharing this habitat. Wild isolates of L. sanfrancisco were initially unable to grow on glucose. Upon growth on maltose such strains required adaptation times of up to 150 h to grow on glucose. After subsequent transfer of glucose‐grown cells to fresh medium the strains resumed growth both on glucose or maltose. They readily lost their ability to grow on glucose upon exposure to maltose. L. sanfrancisco exhibited biphasic growth characteristics on media containing glucose, maltose or both carbon sources. Evidence is provided that biphasic growth and metabolite formation are dependent on the redox potential.